6-Benzylidene-2-[4-(pyridin-3-ylcarboxy)benzylidene]cyclohexanones: A novel cluster of tumour-selective cytotoxins. Issue 7 (1st April 2017) - Panda, Atulya K.; Das, Umashankar; Umemura, Naoki; Sakagami, Hiroshi; Kawase, Masami; Balzarini, Jan; De Clercq, Erik; Dimmock, Stephen G.; Roayapalley, Praveen K.; Dimmock, Jonathan R.
Graphical abstract: Highlights: Novel series of cytotoxins displaying tumour-selective toxicity. Development of SAR and QSAR correlations. The compounds possess drug-like properties. The compounds are well tolerated in a short term screen in mice. The mode of actions include PARP1 cleavage and G0 /G1 cell cycle arrest. Abstract: Novel cytotoxins3 –5 containing the 1, 5-diaryl-3-oxo-1, 4-pentadienyl pharmacophore are disclosed. The compounds in series3 and5 have the potential to liberate niacin which may reduce some of the side effects of antineoplastic compounds.3a -c emerged as the most potent cytotoxic compounds with IC50 values in the low micromolar range against human Molt4/C8 and CEM CD4 + T-lymphocytes as well as murine L1210 leukemia cells. QSAR studies revealed that cytotoxic potencies were negatively correlated with the magnitude of the Hammett sigma values of the aryl substituents. The compounds3a -e displayed tumour-selective toxicity against human HL-60, HSC-2, HSC-3 and HSC-4 neoplasms as compared to human HGF, HPC and HPLF nonmalignant cells. A representative potent compound3a caused PARP1 cleavage and G0 /G1 cell cycle arrest in HSC-2 cells. These compounds are well tolerated in mice at doses up to and including 300 mg/kg of the compounds and no mortalities were noted after 4 h. The stability studies undertaken did not reveal that a representative compound3a underwent hydrolysis to the related phenol2a . Some guidelines for further analog development of the novel esters3 were made.